Water-actuated shape-memory and mechanically-adaptive poly(ethylene vinyl acetate) achieved by adding hydrophilic poly (vinyl alcohol). (January 2018) - Zhang, Zhi-xing; Qi, Xiao-dong; Li, Song-tai; Yang, Jing-hui; Zhang, Nan; Huang, Ting; Wang, Yong
Graphical abstract: Highlights: The EVA/PVA blends exhibited excellent water uptake and dehydration abilities. The absorbed water greatly decreased the modulus of the EVA/PVA blends, which made the samples could realize complicated deformation at gentle force. The E65P35 sample showed excellent water-actuated shape memory effect. Our work provides a facile approach to fabricate materials with water-actuated shape memory effect and mechanically adaptive functions. Abstract: Water-actuated shape memory polymers (SMPs) have great potential applications in many fields. Although many strategies have been developed to endow polymers with water-active shape memory effect (SME), so far it is still challenging to prepare the water-actuated SMPs with a highly sensitive SME in a method as facile as possible. In this work, poly(vinyl alcohol) (PVA) was incorporated into poly(ethylene vinyl acetate) (EVA) through the simple solution compounding processing. The blends exhibited good interfacial interaction on one hand. On the other hand, PVA exhibited excellent reinforcement effect, leading to the great enhancement of modulus and strength. Further results showed that the samples had excellent water uptake and dehydration abilities, and the presence of water resulted in the dramatic decrease of modulus and large increase of tensile ductility, which endowed the materials with great potential to realize complicated deformation at gentle force. The water-active SME was evaluated through cycling measurements, i.e. wetting-stretching-drying processes. The results showed that the water-active SME of the blends was greatly dependent upon the blend compositions. After several cycling measurements, the water-active SME of samples became stable. Specifically, for the sample containing 35 wt% PVA, the shape fixity and shape recovery ratios were increased up to 98.7% and 99.5%, respectively. The mechanisms for the excellent water-active SME were then discussed.